Diving behaviour of sub-adult harbour seals (Phoca vitulina) at Prins Karls Forland, Svalbard - Kovacs, Kit M.; Gjertz, Ian; Krafft, Bjørn; Lydersen, Christian (Norwegian Polar Institute, 2008)
Diving behaviour of sub-adult harbour seals (Phoca vitulina) from Svalbard was studied using time-depth recorders (TDRs, n=3), during the post-moulting period. The TDRs recorded depth and time at 10 s intervals with a depth resolution of 2 m. The seals spent 82±10% of their time in the water and 18±10% of their time hauled out during the autumn study period. Activity patterns were significantly affected by both tidal and light cycles. Most of the dives (n=11,322) were relatively shallow (mean depth 40.6±25.5 m) and of short duration (mean duration 2.6±1.0 min) with maximum depth and duration values of 172 m and 10 min, respectively. The dives were classified into one V- and two U-shaped classes, via PCA and cluster analyses. The most frequent dive type, U 1 -dives, were much deeper, lasted longer, and had longer bottom time and faster ascent and descent rates than the other dive types. Approximately 70% of all dives fell into this category and these dives occurred predominantly in clearly defined bouts. Diving bouts lasted 12.5 h on average and consisted almost entirely of U 1 -dives (97.5%). Harbour-seal foraging in Svalbard, at least that which is performed by juveniles during the autumn, appears to involve dedicated excursions that include very intense diving bouts.